Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Kemampuan Mengindentifikasi Teks Laporan Hasil Observasi Pada Peserta Didik Kelas X SMAN 1 Muara Sugihan - Linda Hernawati; Missriani Missriani; Yessi Fitriani (Jurnal Ilmiah Dikdaya, 2023)
This study aims to apply the discovery learning learning model in improving the ability to identify the text of the observation report for students of SMAN 1 Muara Sugihan. To achieve this goal, the classroom action research was conducted with three cycles. Based on the results of the study, it can be concluded that the application of the discovery learning model can improve the ability to identify the text of the observation report of class XI students of SMAN 1 Muara Sugihan. In cycle I, the action of the first cycle has not been achieved regarding the observation aspect, then in the second cycle, the observed aspects have increased but cannot be said to have reached the KKM, so the researcher takes action in cycle III. In cycle III, all aspects observed experienced an increase from the previous two cycles. The average increase from the results of observations in the learning process cycle I and cycle II increased to thirtysix students or around 51.42%. In this cycle there was an increase to 27.14%. In cycle III there was an increase from the previous two cycles, the proportion achieved was 73.86% (seventythree point eighty six percent) and there were sixty seven students who achieved scores above the KKM. So, the increase achieved was 43.58% (fortythree point five eight percent).